Tarantulas - Randolph, Joanne (New York : PowerKids Press, 2007)
Explores having a tarantula as a classroom pet; discussing picking one out, physical and behavioral characteristics, creating a healthy environment, feeding, and handling.
Includes index.
2.7
K-3
Keywords: Tarantulas as pets -- Juvenile literature; Tarantulas; Pets; Tarantulas; Pets; Tarantulas as pets; Pets